Strategic leadership and moral values and their Relationship to organizational performance among the personnel of sports stadium security in Iraq - Saad Luaipi Fahad Ali Al-saedi; Prof. Dr. AYAD NASER HUSSEIN; Asst. Prof. Dr. Ali Hussain Ali (International Journal of Psychosocial Rehabilitation, 2020)
The study aimed to build three measures of strategic leadership, ethical values and organizational performance of employees of sports stadium security in Iraq, to identify the reality of strategic leadership, ethical values and organizational performance, and to identify the nature of the correlation between strategic leadership and moral values with their organizational performance. Strategic leadership and ethical values in the organizational performance of employees of sports stadium security in Iraq, and the descriptive research method was adopted in the method of relational relations, on a sample of employees of sports stadium security (leaders responsible for ranks), They are the ones who are continuing to organize the maintenance of security and its departments in the stadiums of the Ministry of Youth and International Sports for the sports season (2019-2020), whose number is (592) affiliates, for the period from (12/30/2019 to 2/2/2020), they were all chosen as a total sample. By (100%), then it was divided into three samples (building, exploratory, application) according to the research requirements, and after completing this construction according to sequential systematic steps, the three measures were applied in five governorates (Baghdad, Karbala, Basra, Najaf and Maysan) After processing the study data using the SPSS-V26 system, the researcher concluded that the measures of strategic leadership, ethical values, and organizational performance are suitable for what was built for in the measurement from the point of view of the security personnel of sports stadiums in Iraq, It enjoys the conditions for accepting measurement tools in sports management, and its affiliates possess an acceptable level of strategic leadership, ethical values, and organizational performance that enable them to manage and organize the security aspect in matches that take place in Iraqi sports stadiums. The level of moral values is linked to the level of their organizational performance areas with a high positive relationship. The strategic leadership and ethical values influence and influence their organizational performance positively. The researcher recommends that it is necessary to work to support the Ministry of Interior’s policy in enabling the employees of the security of sports stadiums in Iraq to increase leadership The strategy and moral values of the affiliates because of their positive and important role in increasing the level of effectiveness of organizational performance, It is necessary for those in charge of managing sports stadium security affiliates’ courses to review their approved vision of graduating courses, to increase the level of effectiveness of the scientific and technical capabilities of their outputs based on the results of this study. To deliver lectures within the developmental sports stadium security affiliates’ courses, and the Ministry of Interior must pay attention to support the efforts of academic researchers in the fields of physical education and sports sciences seeking to improve the level of security personnel of sports stadiums in Iraq.